2018
DOI: 10.1177/0734282918760724
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Theoretical Structure of the Differential Ability Scales—Second Edition Through Hierarchical Exploratory Factor Analysis

Abstract: When the Differential Ability Scales-Second Edition (DAS-II) was developed, the instrument's content, structure, and theoretical orientation were amended. Despite these changes, the Technical Handbook did not report results from exploratory factor analytic investigations, and confirmatory factor analyses were implemented using selected subtests across the normative age groups from the total battery. To address these omissions, the present study investigated the theoretical structure of the DAS-II using princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The superiority of general intelligence observed in all four age groups is identical to that found by Canivez et al. () with the total WISC‐V standardization sample and similar to other studies of Wechsler scales using both EFA and CFA methods (Bodin et al., ; Canivez, ; Canivez & Watkins, , ; Canivez et al., ; Dombrowski, Canivez, & Watkins, 2018; Gignac & Watkins, ; Lecerf & Canivez, ; McGill & Canivez, , ; Nelson et al., ; Watkins, ; ; Watkins & Beaujean, ; Watkins et al., , , ) and other intelligence tests (Canivez, ; Canivez & McGill, ; Canivez et al., ; Cucina & Howardson, ; DiStefano & Dombrowski, ; Dombrowski, , , ; Dombrowski & Watkins, ; Dombrowski et al., ; Dombrowski, Golay, McGill & Canivez, ; Dombrowski, McGill, & Canivez, , , ; Dombrowski, McGill, Canivez & Peterson, ; Nelson & Canivez, ; Nelson et al., ). These results are also consistent with the broader professional literature on the importance and dominance of general intelligence (Deary, ; Jensen, ; Lubinski, ; Ree et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…The superiority of general intelligence observed in all four age groups is identical to that found by Canivez et al. () with the total WISC‐V standardization sample and similar to other studies of Wechsler scales using both EFA and CFA methods (Bodin et al., ; Canivez, ; Canivez & Watkins, , ; Canivez et al., ; Dombrowski, Canivez, & Watkins, 2018; Gignac & Watkins, ; Lecerf & Canivez, ; McGill & Canivez, , ; Nelson et al., ; Watkins, ; ; Watkins & Beaujean, ; Watkins et al., , , ) and other intelligence tests (Canivez, ; Canivez & McGill, ; Canivez et al., ; Cucina & Howardson, ; DiStefano & Dombrowski, ; Dombrowski, , , ; Dombrowski & Watkins, ; Dombrowski et al., ; Dombrowski, Golay, McGill & Canivez, ; Dombrowski, McGill, & Canivez, , , ; Dombrowski, McGill, Canivez & Peterson, ; Nelson & Canivez, ; Nelson et al., ). These results are also consistent with the broader professional literature on the importance and dominance of general intelligence (Deary, ; Jensen, ; Lubinski, ; Ree et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…From this review, they made several unsubstantiated claims that are used to support their premises. For example, Decker and colleagues asserted that “no justification was given for the preference of a BF/SL model” (p. 4) for the Differential Abilities Scales, Second Edition (DAS-II; Elliot, 2007) exploratory factor analysis (EFA) conducted by Dombrowski, McGill, Canivez, & Peterson (2019). This characterization is inaccurate.…”
Section: Conceptual Misunderstandingsmentioning
confidence: 99%
“…Dombrowski et al (2020) claim “...ample justification…” (p. 3) has been given in previous studies for using a BF model and SL procedure, and specifically referenced pages 92–93 in Dombrowski, McGill, Canivez, and Peterson (2019) as providing such justification. Readers are encouraged to independently verify this claim; however, the theoretical justification from this reference is difficult to discern.…”
Section: Theoretical Justification For Using a Bf Model Or Sl Procedumentioning
confidence: 99%
“…Rather, the use of a BF model or SL procedure has primarily been justified by noting the omission of these methods in validity studies reported in technical manuals. For example, in noting the omission, Dombrowski et al (2019) suggested the DAS-II technical manual and theoretical structure was “…presently incomplete.” (p. 93). Often embedded as an argument for including both exploratory and confirmatory factor analytic approaches, previous studies are cited (i.e., Canivez & McGill, 2016) as finding structural validity evidence discrepant from results reported in technical manuals.…”
Section: Theoretical Justification For Using a Bf Model Or Sl Procedumentioning
confidence: 99%